Association of Ki-67 Expression and Response of Neoadjuvant Chemotherapy in Invasive Breast Cancer Patients in Bandung - Andri Rezano; Chen En Pan; Afrida Aizzatun Istiqomah; Almira Zada (Faculty of Medicine Universitas Padjadjaran, 2018)
Objective: To analyze the association of Ki-67 expression and response of neoadjuvant chemotherapy in patients with invasive breast cancer. Methods: A retrospective observational study on the association of Ki-67 expression and response of neoadjuvant chemotherapy in patients with invasive breast cancer was conducted. This study included twenty-five female patients with invasive breast cancer who met the inclusion criteria. Parameters analyzed were age, tumor size, and immunohistochemical expression of Ki-67. Size of the tumor at pre- and post-neoadjuvant chemotherapy were obtained in cm3 and compared between 3 groups of Ki-67 expression levels. One way ANOVA was used to perform the statistical analysis. Results: A significant difference in changes of tumor size for Ki-67 level >20% compared to <14% and 14–20% was seen. Based on the result, neoadjuvant chemotherapy was proven to have similar effects in patients with Ki-67 expression of <14% and 14–20% but less effective in patients with Ki-67 expression of >20%. Conclusions: Low to modest expression of Ki-67 was a better biomarker to predict the response of neoadjuvant chemotherapy in patients with invasive breast cancer compared to high expression of Ki-67. However, the cut-off value of 20% could be ideal to predict the outcome of neoadjuvant chemotherapy in patients with invasive breast cancer. DOI: 10.15850/ijihs.v6n2.1374